2017
DOI: 10.14715/cmb/2017.63.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive chemical compounds in Eremurus persicus (Joub. & Spach) Boiss. essential oil and their health implications

Abstract: The genus Eremurus is native to Eastern Europe and temperate Asia. Particularly, Eremurus persicus (Joub. & Spach) Boiss. is highly valued in traditional foods and medicine. Scientific knowledge about E. persicus chemical composition and bioactivity is required. Therefore, the present study is aimed to determine the volatile composition of E. persicus essential oil (EO) by means of gas chromatography coupled to flame ionization/mass spectrometry detection. Moreover, the antioxidant, antimicrobial, anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…Nowadays, various risks factors such as stress, environmental and biodiversity changes, modern life styles and new food habits, immune pressures, and the impact of exploding populations lead to flaring up of common health problems in humans, to increase the frequency of carcinomas and to compromise the immune system. In addition to this, a deadly issue of the present time is the emergence of antibiotic‐resistant pathogens and the toxic effects of residual medicines in the food chain (Dhama et al, ; Kuldeep et al, ; Sharifi‐Rad, Ayatollahi, et al, ; Sharifi‐Rad, Varoni, et al, ; Salehi et al, ). These factors act as the driving force for the search of new medicaments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, various risks factors such as stress, environmental and biodiversity changes, modern life styles and new food habits, immune pressures, and the impact of exploding populations lead to flaring up of common health problems in humans, to increase the frequency of carcinomas and to compromise the immune system. In addition to this, a deadly issue of the present time is the emergence of antibiotic‐resistant pathogens and the toxic effects of residual medicines in the food chain (Dhama et al, ; Kuldeep et al, ; Sharifi‐Rad, Ayatollahi, et al, ; Sharifi‐Rad, Varoni, et al, ; Salehi et al, ). These factors act as the driving force for the search of new medicaments.…”
Section: Resultsmentioning
confidence: 99%
“…From the antioxidant activity measured in plasma, these authors suggested that the antioxidant protection against oxidative stress could occur through a direct antioxidant effect of phenolic metabolites, including thymol sulfate(Rubió et al, 2014).3.3 | Role in health: BioactivityNowadays, various risks factors such as stress, environmental and biodiversity changes, modern life styles and new food habits, immune pressures, and the impact of exploding populations lead to flaring up of common health problems in humans, to increase the frequency of carcinomas and to compromise the immune system. In addition to this, a deadly issue of the present time is the emergence of antibiotic-resistant pathogens and the toxic effects of residual medicines in the food chain(Dhama et al, 2013;Kuldeep et al, 2014;Salehi et al, 2017). These factors act as the driving force for the search of new medicaments.…”
mentioning
confidence: 99%
“…Regarding the volatile compounds, essential oils (EOs) are considered as potential medicinal agents (Salehi et al, ; J. Sharifi‐Rad, Sureda, et al, ; M. Sharifi‐Rad, Varoni, et al, ; M. Sharifi‐Rad et al, ; Yu et al, ). The EOs from Echinacea plants can be obtained from different parts of the plants, such as roots, leaves, flowers, and aerial parts, and with different yields (Mazza & Cottrell, ).…”
Section: Chemical Composition Of Essential Oils Obtained From Echinacmentioning
confidence: 99%
“…Specifically, the antimicrobial effects of multiple plant preparations have been progressively confirmed and supported by both in vitro and in vivo studies and clinical trials [17,18,19,20,21]. Thus, their lower costs, high effectiveness, bioavailability, bioefficacy, and few to no adverse effects have led to intensive research on this topic [22,23,24,25,26,27,28]. …”
Section: Introductionmentioning
confidence: 99%